A case study of an investigation of the effects of English classroom environments to learning outcomes / Mohd Hafiz Mat Adam - Mat Adam, Mohd Hafiz (2015)
Millennials or also known as the Generation Y learners have subjugated universities and colleges at the present time. They have distinct expectations and perceptions toward their contemporary classrooms. This cohort highlighted the different needs for their learning, where traditional classrooms were seen to have only provided well for the Generation X individuals. Generation Y students were seen to be more engaged in modern classrooms that facilitate their needs as Millennials. Forty six of the researcher's students from Faculty of Architectural and Town Planning were chosen as the sample of study. The students belonged from two different classrooms namely language laboratory and traditional classroom. The objective of this research was to find out whether diverse classroom environments influenced students’ performance in English subject, whereby it intended to reveal whether modern classroom students performed better than the traditional classroom students or vice versa. IBM SPSS Statistics 20 software was used to measure the effects based in achieved scores (results) between classroom environment and students’ learning outcomes using descriptive and inferential statistics. The software was used to calculate the significance level, means, B-values and standard deviations using various methods like T-Test. Descriptive Statistics and Regression to determine the accuracy of the data, and finally make conclusions based on the result. The results of the study showed that the different classroom environments had impacted the students’ performances in all four components of the English skills (listening, speaking, reading and writing). The results showed that the significance level of all scores between language laboratory and traditional classroom were all close to 1, where Sig. = .000 (listening), Sig.= .000 (speaking), Sig. = .000 (reading) and Sig. = .020 (writing). The significance results that were based on standard deviations between the two classroom environments showed that the language laboratory students scored better in all assessments compared to the traditional classroom students.